Originally Posted by

**engineerairborne** I I知 trying to understand that algebra in this problem. This is a Proof for checking solutions of recurrence.

I have a sequence defined as sn = 2n+4*3n n[IMG]file:///C:/Users/Owner/AppData/Local/Temp/msohtmlclip1/01/clip_image002.gif[/IMG]0

I have to prove that sn = 5sn-1 -6sn-2

Now the book does this as follows.

5(2n-1 + 4*3n-1) -6(2n-2+4*3 n-2) = (5*2-6) 2n-2 + (5*4*3 -6*4) 3 n-2 =Some other stuff I understand = 2n+4*3n

Where does the n-1 go, I知 not understanding the first part of this algebra?